Characteristics of salivary cortisol and alpha-amylase as psychobiological study outcomes in palliative care research - Warth, Marco; Stoffel, Martin; Köhler, Friederike; Bardenheuer, Hubert J.; Keßler, Jens; Ditzen, Beate (BMC palliative care, 2022)
Background:  Psychosocial interventions are rapidly emerging in palliative care. However, randomized trials often fail to provide evidence for their effectiveness with regard to patient-reported outcomes. Stress biomarkers could complement self-report data, but little is known about their feasibility, acceptance, and interpretability. - Methods:  Therefore, we designed a randomized crossover trial in which 42 patients in a palliative care unit participated in both a brief mindfulness intervention (MI) and a resting state control condition (CC) on two consecutive afternoons. On each day, we collected four saliva samples in 20-min intervals using S alivettes© to determine salivary cortisol (sCort) and alpha-amylase (sAA) concentration levels. At all measurement points, self-rated well-being and stress as well as cardiovascular markers were assessed. Baseline measurements further included self-rated quality of life and clinician-rated functional status. - Results:  78.6% of the patients provided the maximum number of 8 saliva samples and 62.2% reported no subjective difficulties with the sampling procedures. 66.6% (sCort) and 69.6% (sAA) of all possible samples were finally included in the analysis. Xerostomia and nausea were the main reasons for missing data. Higher sCort levels were associated with higher heart rate and lower quality of life, functional status, and heart rate variability. Corticosteroid and sedative medication as well as time since last meal were identified as potential confounders. Regarding reactivity to the MI, we found an overall decrease in sCort levels over time (b = -.03, p = .01), but this effect did not differ significantly between the study conditions (b = .03, p = .21). sAA levels were higher in men than in women. Trajectories over time did not significantly differ between the two conditions (b = -.02, p = .80) and associations with other stress and health-related constructs were weak. - Conclusions:  Findings indicate that sCort might serve as a psychobiological outcome in future palliative care trials. However, future research should refine the exact measurement and conceptualization strategies for sCort in palliative care research. High attrition rates should be expected in patients with xerostomia or nausea. Trial Registration:  Registered at the German Clinical Trials Registry (DRKS00013135) at 04/12/2017.